New Stability Indicating Liquid Chromatographic Method for the Determination of Eplerenone in the Presence of Internal Standard - Annapurna, Mukthinuthalapati Mathrusri (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: A simple stability indicating reverse-phase high-performance liquid chromatographic (RP-HPLC) method has been developed for the determination of Eplerenone (EPL) in its tablet dosage forms. EPL is an aldosterone antagonist. It is administered either alone or in combination with other drugs to treat cardiovascular diseases. Materials and Methods: EPL was eluted on SHIMADZU HPLC system using Agilent column (150 mm × 4.6 mm i.d., 3.5 μm particle size) (isocratic mode). A mixture of 10 mM tetra butyl ammonium hydrogen sulfate and methanol (30: 70, v/v) was used for the chromatographic separation and was monitored at 242 nm (PDA detector) with flow rate 1.0 mL/min. The total run time was 10 min. Forced degradation studies were performed, and the method was validated. Results and Discussion: EPL has obeyed Beer-Lambert’s law 0.1–40 μg/mL with correlation coefficient 0.9996. The limit of detection and limit of quantification are found to be 0.0283 μg/mL and 0.0846 μg/ mL, respectively. EPL was found to be highly resistant toward hydrolysis and acidic conditions. Conclusions: It is observed that this RP-HPLC method is accurate, precise, sensitive, and reproducible for the estimation of EPL in tablets. The method was validated as per the ICH guidelines and very much specific and selective.